Endogenous inotropic factor-induced endothelium-dependent relaxation of vascular smooth muscle. - Han, C. (1996)
1. Possible contractile or relaxation effects of an endogenous inotropic factor (EIF) isolated and purified from porcine heart left ventricle were examined in rat isolated aortic ring preparations. 2. EIF induced a dose-dependent relaxation of the rat isolated aortic ring preparation pre-contracted with 0.4 microM phenylephrine (PE); 200 microliters (in 5 ml bath) of EIF caused relaxation of aortic rings by as much as 67.4 +/- 4.5%. In another set of experiments, in the presence of 100 microliters EIF, the PE concentration-response contractile curve shifted to the right, the maximal contractile force was reduced by as much as 32.8% and the EC50 of PE increased from 0.2 to 0.3 microM. 3. The relaxation effect of EIF was demonstrated to be endothelium-dependent. Additional experiments demonstrated that EIF-induced relaxation in an isolated aortic ring could be inhibited by 2 microM NG-nitro-L-arginine methyl ester, a nitric oxide synthase inhibitor, suggesting the involvement of nitric oxide in EIF-induced relaxation of the muscle. 4. Atropine (0.2 microM) or indomethacin (10 microM) had no significant effect on EIF-induced relaxation. 5. These data suggest that EIF, a novel endogenous inotrope from porcine myocardium, also acts as an endothelium-dependent vasodilator substance mediating relaxation in the rat isolated aorta mainly by release of nitric oxide. The possibility of EIF acting through muscarinic receptor and the involvement of prostacyclin were excluded.